Management turnover across the corporate hierarchy - Fee, C.Edward; Hadlock, Charles J (Journal of Accounting and Economics, 2004)
We study management turnover for the top five executives in a sample of 443 large firms from 1993 through 1998. The rate of forced turnover for non-CEOs is at least as great as that for CEOs, but the sensitivity of turnover to firm performance is smaller for non-CEOs. The probability that a non-CEO leaves office is elevated around CEO dismissals, particularly when the replacement CEO is an outsider. Many dismissed executives obtain new employment, but on average their new positions are significantly inferior to their prior jobs. Labor market outcomes are related to past compensation and the circumstances around departure.